Perfil epidemiológico da Leishmaniose no estado do Paraná – 2001 a 2017 - Bassotto, Dayane (2020)
Neglected Tropical Diseases are defined as a group of twenty-one diseases caused by infectious agents or parasites. Leishmaniasis is a NTD transmitted by the bite of infected sandflies that in the most severe form, visceral leishmaniasis, attacks the internal organs and in the most prevalent form, the skin, causes facial ulcers and disfiguring scars. A cross-sectional analytical observational study was carried out with the objective of determining the epidemiological profile of patients with American Tegumentary Leishmaniasis (ATL) in the state of Paraná from 2001 to 2017, through data collection in the Notifiable Diseases Information System. During the study period, 8444 cases of ATL were notified and confirmed. The profile of confirmed cases found was white men of working age (29 to 50 years), with low education and residents of the urban area. The origin of cases is indigenous to both the reporting municipality and the state. Regarding the form of the disease, most of them were cutaneous leishmaniasis, with clinical laboratory diagnosis and the evolution of the cases is mostly curable. The data of the work aim to elucidate the forms of improvements in health policies, also to demonstrate in which places measures should be taken to control and even eradicate the disease.